Effect of Marshall Characteristics with The Addition of Polyethylene Terephthalate (PET) Waste as a Filler Mixture in Asphalt - Maulida Nurfitria; Mutiara Anggraeni; M. Arif Firman Nugroho; Martinus Agus S (Riviera Publishing, 2025)
Asphalt pavement is one of the main elements of transportation infrastructure. However, asphalt pavements often suffer from damage such as cracking, plastic deformation and peeling due to the influence of traffic loads and extreme temperature changes. With the extensive use of plastics in daily life leading to an increase in plastic waste which has become one of the serious problems in Indonesia, an alternative is needed to deal with the problem. By modifying the asphalt filler using Polyethylene Terephthalate (PET) waste, the AC - WC asphalt layer is one way to increase the stability of the road structure. The purpose of this study is to determine the comparison of the value of marshall characteristics in the AC-WC layer with the addition of Polyethylene Terephthalate (PET) waste filler fixed at 7%, and Polyethylene Terephthalate (PET) waste varies by 6%, 6.5%, 7%, 7.5%, and 8%, and analyze the addition of PET plastric waste to the value of Marshall characteristics as a mixture of asphalt filler in the AC - WC layer. The method used in this research is the experimental method, using a control variable at 5.3% asphalt content with a fixed PET combination of 7%. Based on the results of the study that the addition of PET waste in the AC-WC asphalt mixture has an influence on the marshall characteristics, it can be seen from the values of Stability, Flow, VIM, VFM, VFB, and Marshall Quentiont which have changed.